Tooth Tip Interference and Stress Analysis of High Contact Ratio Spur Gear Pairs Using an Optimized Design Tool - Hüseyin Enes Salman; Samet Turan (MANAS: Journal of Engineering)
Gears are structural elements that function to transmit power in mechanical systems. The power transmission is carried out by the rolling motion of the teeth pair. The average number of teeth that come into contact while the gears are running is called the contact ratio and this value is generally between 1 and 2 for gears with standard profile. As the number of teeth of the gear increases, the contact ratio may exceed 2, and the gears with a contact ratio greater than 2 are called high contact ratio (HCR) gears. For HCR gears, there is a higher risk of tooth tip interference when compared to the standard gears and they require contact point calculation to avoid interference. In this study, a mathematical tool is developed using MATLAB to analyze and avoid tool tip interference in HCR spur gears. The addendum diameter, dedendum diameter, pressure angle and modulus values are optimized using the developed mathematical tool in order to obtain an HCR geometry with minimal volume and no tip interference. In addition, the spur gear stresses are calculated using the AGMA standards. According to the results, it has been analytically proven that the load carrying capacity of the HCR spur gear is higher than that of the standard gear with the same diameter and volume. The developed optimization tool provided accurate and optimized geometries for the analyzed HCR spur gears.